Diversity, Distribution and Morphology of Wild Mushrooms Collected from Gajni Forest of Bangladesh - Afrin Joty, Arifa; Aminuzzaman, F. M.; Sultana, Nazneen; Tanjina, Akter; Sonchita, Debosri Rani Biswas; Islam, Md. Nurul (International Journal of Environment, 2020)
A survey was carried out in Gajni forest from June to August of 2017 and 2018 to document the diversity, distribution and morphological characterization of wild mushrooms. A total of 32 mushroom samples were collected and identified to 28 species belonging to 11 genera, under 8 families. Ganoderma sp. was found abundantly in the survey area among the other collected species and it exhibited the maximum frequency of occurrence (75%), whereas the maximum density (20.50%) was recorded for Agaricus bitorquis and the dominant host was Shal tree (Shorea robusta). The dominant genera were Ganoderma, Agaricus, Trametes, Volvariella and Amanita. The dominant family of collected wild mushrooms was Ganodermataceae followed by Polyporaceae, Agaricaceae, Amanitaceae, Rusullaceae, Pluteaceae, Marasmiaceae and Strophariaceae. Among collected species, 5 species were found edible, 12 species had medicinal value and 11 species were inedible, poisonous or of unknown importance. The specimens were deposited to the Sher-e-Bangla Agricultural University Herbarium of Macro Fungi (SHMF). This is a report of wild mushrooms diversity and their distribution in the Gajni forest region of Bangladesh. This study was asserted that a wide range of mushroom plays an important role in the ecosystem of Gajni forest and might be useful in food and industry sector in future.